Preparation method of antibacterial corrosion-resistant titanium alloy surface composite structure

Through a single laser combined with nanosecond laser processing and laser defocus irradiation technology, the microtexture and nanostructure of the titanium alloy surface were prepared, solving the problems of complex process and chemical pollution in the existing technology, and improving antibacterial corrosion resistance and anti-fouling biological adhesion effect.

CN120421922APending Publication Date: 2025-08-05UNIV OF SHANGHAI FOR SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510633332.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-16
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

The prior art requires the use of different equipment and processes when preparing antibacterial corrosion-resistant titanium alloy surface composite structures, resulting in complex processes and chemical contamination. The wetting changes in the laser-induced periodic structure after ultraviolet irradiation weakens the antibacterial performance.

Method used

A single laser is used for nanosecond laser processing and laser defocus irradiation, and a microtexture and nanostructure are prepared to form a composite structure on the surface of the titanium alloy, avoiding chemical pollution and improving antibacterial corrosion resistance.

Benefits of technology

The composite structure with strong corrosion resistance and excellent antibacterial properties on the surface of titanium alloy is realized. The process is simple and chemical pollution is free, which significantly improves the anti-fouling biological adhesion performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120421922A_ABST
    Figure CN120421922A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an antibacterial and corrosion-resistant titanium alloy surface composite structure. The preparation method comprises the following steps: S1, pretreating a titanium alloy plate; s2, the titanium alloy plate is subjected to nanosecond laser processing to prepare a microstructure; s3, the titanium alloy plate is subjected to laser out-of-focus irradiation processing to prepare a nano structure, and a composite structure on the surface of the titanium alloy plate is formed; according to the preparation method of the antibacterial corrosion-resistant titanium alloy surface composite structure, a single laser is adopted, a micro-texture and a nano-structure on the surface of the titanium alloy can be machined, the composite structure with high corrosion resistance and excellent antibacterial performance on the surface of the titanium alloy is formed, the process is simple, preparation is easy, and chemical pollution is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an antibacterial and corrosion-resistant titanium alloy surface composite structure technology, in particular to a preparation method of the antibacterial and corrosion-resistant titanium alloy surface composite structure. Background Art

[0002] In marine environments, metal surfaces are often susceptible to biofilm adhesion. This not only increases a ship's resistance and fuel consumption, but also accelerates corrosion, potentially degrading the performance of moving parts and instruments, and in severe cases, even threatening their proper function. Biofilm adhesion is a gradual process, beginning with the formation of a regulatory film, followed by the attachment of microorganisms, algae, and protozoa, and ultimately, the colonization of large fouling organisms. Therefore, preventing the formation of biofilms on metal surfaces is crucial for maintaining equipment performance and extending its service life.

[0003] In recent years, ultrashort laser pulse technology (pulse width less than 10 picoseconds) has attracted much attention due to its ability to induce periodic surface structures, effectively inhibiting the adhesion of various bacteria (such as Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Streptococcus mutans). The effectiveness of this technology depends largely on the optimization of micro-nanostructures, surface chemistry, and wettability. New technologies for laser-induced micro-nanostructuring (such as DLIP, UV lasers, and beam shaping) can achieve precise control of these key factors, thereby enhancing the applicability of ultrafast laser surface modification in areas such as food and medical implants.

[0004] However, an often overlooked factor is the impact of long-term exposure of metal materials to ultraviolet (UV) radiation in marine environments. Existing research has shown that the surface energy of laser-induced surfaces increases significantly with prolonged UV irradiation, causing the surface properties to transform from superhydrophobic to hydrophilic. Previous studies have indicated that the same laser-induced periodic structure (LIPSS) can lead to varying degrees of bacterial adhesion under different wettability conditions. Therefore, this transformation may weaken the antibacterial properties of LIPSS. Furthermore, research on the effect of the reduced contact angle of LIPSS surfaces after UV irradiation on bacterial adhesion remains insufficient.

[0005] In order to solve the above problems, the surface of titanium alloy needs a composite microtexture and nanostructure. However, the composite structure generally requires the use of laser microtexturing technology to form the microtexture, and then the acid etching process to form the nanostructure. Different equipment is required, the process is complex, the preparation efficiency is poor, and there is serious chemical pollution. Summary of the Invention

[0006] In order to solve the defects of the above-mentioned prior art, the present invention provides a method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure. A single laser is used to achieve the combination of microtexture and nanostructure to form a composite structure with strong corrosion resistance and excellent antibacterial properties on the titanium alloy surface. The process is simple, the preparation is simple, and there is no chemical pollution.

[0007] To achieve the above technical objectives, the present invention adopts the following technical solution: a method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure, comprising the following steps:

[0008] S1, pretreatment of titanium alloy plate;

[0009] S2, nanosecond laser processing of titanium alloy plate to prepare microtexture;

[0010] S3. The titanium alloy plate is subjected to laser defocused irradiation processing to prepare a nanostructure, thereby forming a composite structure on the surface of the titanium alloy plate.

[0011] Preferably, the step S1 specifically includes:

[0012] s1. Cutting: Use laser cutting machine to cut materials;

[0013] s2. Grinding: Use a surface grinder to grind the material surface until the roughness Ra is less than 0.1μm;

[0014] s3. Cleaning: Use ethanol and deionized water to clean the material in an ultrasonic cleaner for 10 minutes;

[0015] s4. Drying: Dry the material naturally.

[0016] Preferably, the method further includes a detection step, which specifically includes:

[0017] A. Cutting to form samples;

[0018] B. Surface morphology analysis;

[0019] C. Surface chemical analysis;

[0020] D. Corrosion resistance test;

[0021] E. Bacterial adhesion test;

[0022] F. Seawater immersion test;

[0023] G. Statistical analysis.

[0024] Preferably, the step A specifically includes:

[0025] Three sample groups of 10 mm × 10 mm × 1 mm, 20 mm × 20 mm × 1 mm, and 35 mm × 45 mm × 3 mm were cut from the material;

[0026] 10 mm × 10 mm × 1 mm samples were used for surface morphology analysis, surface chemistry analysis, and corrosion resistance testing;

[0027] Samples of 20 mm × 20 mm × 1 mm were used for bacterial adhesion testing;

[0028] A 35 mm × 45 mm × 3 mm sample was used for the ocean immersion test and a hole with a diameter of 3 mm was drilled on one edge.

[0029] Preferably, the surface morphology analysis includes scanning electron microscopy, ultra-depth of field microscopy and atomic force microscopy; the scanning electron microscopy is used to observe the surface morphology of the sample with an acceleration voltage of 15kV; the ultra-depth of field microscopy is used to measure the average roughness, depth and diameter of the microtexture of the sample; and the atomic force microscopy is used to evaluate the surface roughness and geometric dimensions of the nanostructure of the sample.

[0030] Preferably, the surface chemical analysis includes X-ray photoelectron spectroscopy and X-ray diffraction detection. The X-ray photoelectron spectroscopy is used to analyze the chemical composition of the sample surface, including narrow spectra of C1s, Ti2p and O1s; and the X-ray diffraction is used to determine the phase composition of the sample.

[0031] Preferably, the corrosion resistance test includes a corrosion performance potentiodynamic polarization test and an electrochemical impedance spectroscopy test.

[0032] The corrosion performance potentiodynamic polarization test uses an electrochemical workstation; the corrosion solution is artificial seawater, which contains 25.5g / L sodium chloride, 3.2g / L magnesium sulfate, 1.3g / L calcium chloride, and 0.7g / L potassium chloride. In the test system, a carbon rod serves as a working electrode, Ag / AgCl serves as a reference electrode, and the sample serves as a working electrode. The scan rate is 5mV / s, and the scan range is -1400mV to 400mV. The sample needs to be immersed in the corrosion solution for 30 minutes before the test is terminated, and the equilibrium potential, corrosion current, cathode Tafel slope, anodic Tafel slope, and polarization resistance Rp are calculated by extrapolation.

[0033] The electrochemical impedance spectroscopy test is performed in a frequency range of 100 kHz to 1 Hz, with a sinusoidal potential change of 5 mV applied to the sample.

[0034] Preferably, the step E specifically includes:

[0035] Bacterial adhesion: Titanium alloy was placed in a 24-well plate and incubated at 121°C, 1.1×10 5Sterilize in an autoclave at a pressure of Pa for 20 min; select Staphylococcus aureus and culture it in Luria-Bertani medium for 18 h; dilute the bacterial colony to 1×10 6 A bacterial suspension was formed in fresh culture medium with a concentration of 100 CFU / mL; 300 μL of the bacterial suspension was added to the well plate and incubated at 37°C for 24 hours; 20 μL of the incubated bacterial suspension was aspirated as a sample; each sample was washed with PBS and sonicated in 10 mL of normal saline for 5 minutes; 100 μL of the bacterial suspension was removed from each sample and cultured on an agar plate to determine the antibacterial properties; the suspension on the sample in the well plate was removed at the same time, and the bacteria on the sample surface were fixed with 3% glutaraldehyde; the sample was dehydrated using a gradient dehydration method; the metal surface was gold-plated, and the morphology of the bacteria was observed using a scanning electron microscope;

[0036] Bacterial cell viability test: Combined with SYTO 9 green fluorescent nucleic acid dye and propidium iodide, the survival rate of bacterial cells on different surfaces of the sample was evaluated;

[0037] Contact angle measurement: Use a contact angle meter to obtain images of the contact state of the bacterial suspension on the material surface.

[0038] Preferably, the step F comprises:

[0039] Before immersing in seawater, the samples were weighed in a dry state; the samples were suspended in the seawater, more than 0.5 meters below the water surface at low tide. After 6 months of testing, the samples were removed from the seawater, dried, and weighed again; after weighing, the sample surface was gold-plated, and the morphology of the attached organisms on the sample surface was observed using a scanning electron microscope, and the length, area, and number of the main attached organisms were quantified using ImageJ software.

[0040] In summary, the present invention has achieved the following technical effects:

[0041] The method for preparing the titanium alloy surface composite structure of the present invention uses a single laser to process the microtexture and nanostructure of the titanium alloy surface, forming a composite structure with strong corrosion resistance and excellent antibacterial properties on the titanium alloy surface. The process is simple, the preparation is simple, and there is no chemical pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a schematic diagram of the laser processing process of the present invention;

[0043] Figure 2 is the SEM image of the surface morphology of each group of samples of the present invention;

[0044] Figure 3 It is the Ti2p spectrum of each group of samples of the present invention;

[0045] Figure 4 It is the O1s spectrum of each group of samples of the present invention;

[0046] Figure 5 It is the chemical composition diagram of each group of samples of the present invention;

[0047] Figure 6 It is the electrochemical test diagram of the present invention;

[0048] Figure 7 It is a Staphylococcus aureus culture diagram of the present invention;

[0049] Figure 8 is a SEM image of Staphylococcus aureus adhesion of the present invention;

[0050] Figure 9 It is the staining image of live bacterial cells and dead bacterial cells of the present invention;

[0051] Figure 10 This is a diagram showing the effect of detail dimensions on cell membrane deformation parameters of the present invention;

[0052] Figure 11 is an optical image of marine fouling organisms attached to the surface of a material according to the present invention;

[0053] Figure 12 is an SEM image of marine organisms attached to the surface of the material of the present invention; DETAILED DESCRIPTION

[0054] The present invention will be further described in detail below with reference to the accompanying drawings.

[0055] A method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure comprises the following steps:

[0056] S1. Pretreatment of titanium alloy plates:

[0057] s1. Cutting: Use laser cutting machine to cut materials;

[0058] s2. Grinding: Use a surface grinder to grind the material surface until the roughness Ra is less than 0.1μm;

[0059] s3. Cleaning: Use ethanol and deionized water to clean the material in an ultrasonic cleaner for 10 minutes;

[0060] s4. Drying: Let the material dry naturally.

[0061] S2, nanosecond laser processing of titanium alloy plate to prepare microtexture;

[0062] S3. The titanium alloy plate is subjected to laser defocused irradiation processing to prepare a nanostructure, thereby forming a composite structure on the surface of the titanium alloy plate.

[0063] The number of scans (N) is controlled to prepare microstructures at different depths.

[0064] The samples after pretreatment were designated as group P.

[0065] Nanosecond laser processing forms microtextures, which are divided into shallow pit process and deep pit process. The samples processed by shallow pit process are designated as T1 group, while the samples processed by deep pit process are designated as T2 group ( Figure 1 (a)).

[0066] The samples prepared by laser defocused irradiation process are defined as group S ( Figure 1 (b)).

[0067] The combination of nanosecond laser processing and laser defocused irradiation technology enables the preparation of composite structures on shallow pits and deep pits, which are designated as ST1 group and ST2 group respectively. Figure 1 (c)).

[0068] The detailed information of the three process parameters is shown in Table 1;

[0069]

[0070] As can be seen from Table 1 above, the depth of microtexture is deeper than that of nanostructure. Therefore, microtexture must be done first, and then nanostructure. This order can prevent the latter process from affecting the structure of the former process.

[0071] The detection step specifically includes:

[0072] A. Cutting to form samples:

[0073] Three sample groups of 10 mm × 10 mm × 1 mm, 20 mm × 20 mm × 1 mm, and 35 mm × 45 mm × 3 mm were cut from the material;

[0074] The first sample group of 10 mm × 10 mm × 1 mm was used for surface morphology analysis, surface chemical analysis, and corrosion resistance testing;

[0075] The second sample set of 20 mm × 20 mm × 1 mm was used for bacterial adhesion testing;

[0076] The third sample set of 35 mm × 45 mm × 3 mm was used for the ocean immersion test and had a 3 mm diameter hole drilled on one edge.

[0077] B. Surface morphology analysis: The surface morphology analysis includes scanning electron microscopy (SEM), ultra-depth of field microscopy, and atomic force microscopy (AFM). The SEM is used to observe the surface morphology of the sample at an accelerating voltage of 15 kV. The ultra-depth of field microscopy is used to measure the average roughness, depth, and diameter of the microtexture of the sample. The AFM is used to evaluate the surface roughness and geometric dimensions of the nanostructure of the sample.

[0078] C. Surface chemical analysis: The surface chemical analysis includes X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). The X-ray photoelectron spectroscopy is used to analyze the chemical composition of the sample surface, including narrow spectra of C1s, Ti2p, and O1s; and the X-ray diffraction is used to determine the phase composition of the sample.

[0079] D. Corrosion resistance test: The corrosion resistance test includes a potentiodynamic polarization (PDP) test and an electrochemical impedance spectroscopy (EIS) test. The corrosion resistance test uses an electrochemical workstation. The corrosion solution is artificial seawater, which contains 25.5 g / L sodium chloride, 3.2 g / L magnesium sulfate, 1.3 g / L calcium chloride, and 0.7 g / L potassium chloride. In the test system, a carbon rod serves as the working electrode, Ag / AgCl serves as the reference electrode, and the sample serves as the working electrode. The scan rate is 5 mV / s, and the scan range is -1400 mV to 400 mV. The sample needs to be immersed in the corrosion solution for 30 minutes before the test is terminated. The equilibrium potential, corrosion current, cathode Tafel slope, anodic Tafel slope, and polarization resistance Rp are calculated by extrapolation. The electrochemical impedance spectroscopy test applies a sinusoidal potential change of 5 mV to the sample within a frequency range of 100 kHz to 1 Hz.

[0080] E. Bacterial adhesion test:

[0081] Bacterial adhesion: Titanium alloy was placed in a 24-well plate and incubated at 121°C, 1.1×10 5 Sterilize in an autoclave at a pressure of 1.5 Pa for 20 min. Select Staphylococcus aureus (ATCC25923, purchased from Thermo Fisher Scientific) and culture in Luria-Bertani medium for 18 h. Dilute the bacterial colony to 1×10 6A bacterial suspension was formed in fresh culture medium with a concentration of 100 CFU / mL; 300 μL of the bacterial suspension was added to the well plate and incubated at 37°C for 24 hours; 20 μL of the incubated bacterial suspension was aspirated as a sample; each sample was washed with PBS and sonicated in physiological saline (10 mL) for 5 minutes; 100 μL of the bacterial suspension was removed from each sample and cultured on an agar plate to determine the antibacterial properties; the suspension on the sample in the well plate was removed at the same time, and the bacteria on the sample surface were fixed with 3% glutaraldehyde; the sample was dehydrated using a gradient dehydration method (50% to 100%); the metal surface was gold-plated, and the morphology of the bacteria was observed using a scanning electron microscope;

[0082] Bacterial cell survival test: Combined with SYTO9 green fluorescent nucleic acid dye and propidium iodide (PI), the survival rate of bacterial cells on different surfaces of the sample was evaluated;

[0083] Contact angle measurement: A contact angle meter (OCA15EC, DataPhysics, Germany) was used to obtain images of the contact state of the bacterial suspension on the material surface.

[0084] F. Seawater immersion test:

[0085] Marine immersion testing of the materials was conducted at the Nanshan Port terminal in Sanya, China. Titanium alloy plates were laser-treated on both sides and then suspended in seawater, with the samples located more than 0.5 meters below the water surface at low tide. The testing period was scheduled to begin on February 26, 2024, and end on August 27, 2024, based on the UTC+8 time zone. The samples were weighed in their dry state before immersion. After six months of suspension in the seawater, with the samples located more than 0.5 meters below the water surface at low tide, the samples were removed from the seawater, dried, and weighed again. Following weighing, the samples were gold-plated. Scanning electron microscopy was used to observe the morphology of attached organisms, and ImageJ software was used to quantify the length, area, and number of the main attached organisms.

[0086] G. Statistical analysis: To ensure the reproducibility of key results, at least three samples were prepared for each sample group (P group, T1 group, T2 group, S group, ST1 group, and ST2 group) to evaluate surface geometry, bacterial adhesion test, and seawater immersion test.

[0087] The equipment includes:

[0088] The laser was a nanosecond ultraviolet laser (Poplar-355, Huari, China) with a wavelength of 355 nm, a pulse width of 50 ns, and a rated power of 18 W.

[0089] The surface morphology of the materials was examined using a scanning electron microscope (EVO18, Zeiss, Germany) with an accelerating voltage of 15 kV and a secondary electron detector.

[0090] To measure the average roughness (Ra) of the profile and the depth and diameter of the micropits, the textured surfaces (groups T1, T2, ST1, and ST2) were analyzed using an ultra-depth-of-field microscope (VHX-7000, Keyence, Japan). The test area was 300 μm × 300 μm.

[0091] Because ultra-depth-of-field microscopy cannot accurately measure the width and depth of the milled grooves (P group) and nanostructures (S group), atomic force microscopy (DimensionIcon, BRUKER, Germany) was used to evaluate surface roughness and geometric dimensions. The test area was 20 μm × 20 μm.

[0092] The chemical composition of the sample surface was analyzed using an X-ray photoelectron spectrometer (Escalab 250Xi, Thermo Fisher Scientific, USA). This included acquiring full XPS spectra as well as narrow-band spectra for C1s, Ti2p, and O1s. The full spectra were analyzed using Avantage software to determine the elemental composition. The C-C peak in the C1s spectrum was corrected to 284.8 eV, and the remaining narrow-band spectra were also corrected.

[0093] The phase composition of the materials was determined using an X-ray diffractometer (MiniFlex, Rigaku Corporation, Japan). The 2θ range was set to 30–90°, with a scan rate of 1° / min. Phase composition was analyzed using MDI Jade9 software. The International Center for Diffraction Data (ICDD) PDF card numbers for titanium are JCPDS: 01-1197, and for TiO: JCPDS: 89–5010.

[0094] analyze:

[0095] Figure 2 SEM images of the surface morphology: (a) polished (P group); (b) shallow pits (T1 group); (c) deep pits (T2 group); (d) nanostructures (S group); (e) composite texture of shallow pits and nanostructures (ST1 group); (f) composite texture of deep pits and nanostructures (ST2 group)

[0096] Figure 2 (a) shows the sample surface obtained by plane grinding. The image shows the grinding direction and the irregular scratches formed on the sample during storage and transportation.

[0097] Figure 2 (b) shows the micro-pit array formed after nanosecond laser processing of titanium alloy. The material in the pit migrates from the center to the periphery due to the combined effect of Marangoni convection and surface tension. Figure 2(b) In the enlarged image in the upper right corner, a slight protrusion can be clearly observed at the edge of the pit. The inner surface of the pit also shows a certain degree of smoothing. In addition, some tiny droplet-like structures can be observed on the surface, which are formed during the droplet sputtering process.

[0098] Figure 2 (c) shows the process of further deepening the microstructure formation through multiple scans. As the number of scans increases, the possibility of micropores connecting with each other also increases.

[0099] Figure 2 (d) shows the surface morphology formed using a high-energy laser defocused irradiation process, with two typical features clearly appearing: nanotrench and nanopillar. When a high-energy laser is irradiated onto a surface in a defocused manner, the area affected by a single laser pulse increases while the energy density in the depth direction decreases. This laser action causes the surface material to rapidly melt and solidify, while the temperature difference between the surface and subsurface layers generates thermal stress at their interface, which in turn promotes the formation of nanostructures.

[0100] Nanostructures can be successfully fabricated on microstructured surfaces using laser defocusing methods (see Figure 2 (e) and (f)). A major advantage of this laser irradiation method is that it can preserve the original micron-scale micro-texture morphology while making the texture surface smoother (see Figure 2 (e) and (f)).

[0101] Figure 3 Ti2p spectrum. (a) P; (b) T1; (c) T2; (d) S; (e) ST1; (f) ST2;

[0102] Figure 3 The Ti2p spectrum obtained by fitting the binding energy is shown. 3+ and Ti 4+ state.

[0103] (a) (b) TiO2 is the main component (74% and 77%), followed by Ti2O2 (26% and 23%), indicating that the titanium in these two samples is mainly Ti 4+ Form exists, part is Ti 3+ state.

[0104] (c): The proportion of TiO2 dropped to 39%, Ti2O2 was 24%, and 37% of the Ti-xAl-yO phase appeared (in the system where Ti and Al coexist, Ti and Al can combine with oxygen to form their own oxides, such as TiO2 and Al2O2. Under certain conditions, these oxides may be connected by bridging oxygen atoms to form a composite structure, such as Tix Al γ O)

[0105] (d) The proportion of Ti-xAl-yO increases to 64%, while TiO2 decreases to 17%, and Ti2O2 also reaches 19%, indicating a significant interaction between titanium and aluminum.

[0106] (e) and (f) are mainly composed of TiO2, without other obvious peaks.

[0107] The above results show that the processing of the deep pit T2 and the nanostructured S groups will cause the Al and O elements in the titanium alloy to combine. It should be noted that the surface binding energy of the T2 and S groups is higher than that of the Ti 4+ The peak position ( Figure 3 (c) and (d) This is likely due to the formation of a dense oxide layer on the surface of the material during laser treatment. Furthermore, the uneven charge distribution between the surface and the interior of the material can lead to band bending, which affects the emission and detection of surface electrons.

[0108] However, the peak observed at about 468 eV is unlikely to be a direct splitting peak of the Ti2p orbital. 2 / 2 and Ti 2p 2 / 2 The energy difference between these energy levels is insufficient to produce such a significant energy shift. Therefore, this peak may represent a specific chemical state in a compound formed by titanium (Ti) and other components. It may also be caused by a shift in binding energy due to factors such as charge effects or band bending.

[0109] Figure 4 O1s spectrum. (a) P; (b) T1; (c) T2; (d) S; (e) ST1; (f) ST2

[0110] (a)(b): The main components are CO (50% / 47%) and TiO2 (31% / 30%), with a small amount of Ti2O2 and Al2O2, indicating that there is a large amount of carbon and oxygen contamination on the surface (such as adsorbed water or organic matter).

[0111] (c): The Al2O2 content increased significantly (62%), and the TiO2 decreased to 19%, indicating that the aluminum doping level in this sample was high and the titanium-oxygen ratio was reduced.

[0112] (d): TiO2 is only 5%, while Ti2O2, Al2O2 and C=O are the main components, indicating that titanium is almost reduced or replaced by aluminum.

[0113] (e), (f): Al2O2 and TiO2 are the main components, which is consistent with the Ti 2p analysis ( Figure 4 (e) and Figure 4 The results of (f)) are consistent, especially in (f), TiO2 44%, Al2O2 43%, indicating that Ti and Al coexist in the oxide.

[0114] The O1s spectrum provides evidence for the conclusion that TiO2 is the main component of the Ti2p spectrum (see Figure 4 (a) and Figure 4 (b)). The fitting results of O1s peak in the composite structure (ST1 group and ST2 group) ( Figure 4 (e) and Figure 4 (f)) also shows that TiO2 is the main component, which is consistent with the previous Ti2p analysis ( Figure 3 (e) and Figure 3 (f)).

[0115] Figure 5 Chemical composition of the material. (a) XRD; (b) surface composition and subsurface phase

[0116] The research also used X-ray diffraction (XRD) test to analyze the phase composition of the material. Figure 5 As shown in (a), it can be observed that the diffraction peaks of the P, T1, and T2 groups are roughly located at the same position. However, compared with the P group, the diffraction peaks of the laser microstructured surfaces (T1 and T2 groups) are generally shifted to higher angles. This is mainly because the laser microstructuring process causes stress, resulting in lattice distortion and a decrease in the lattice constant.

[0117] The shift of the diffraction peak toward higher angles generally indicates compressive stress on the material surface, which is beneficial for improving the mechanical properties of the material. Furthermore, the increase in the diffraction peak width of the T2 group indicates surface grain refinement.

[0118] The diffraction peak distributions of the S, ST1, and ST2 groups are relatively similar. Compared with the P, T1, and T2 groups, the diffraction peaks of these groups are also generally shifted to higher angles, indicating that the oxidation treatment further promotes the increase of surface compressive stress in the material.

[0119] Figure 6 Results of electrochemical tests. (a) Tafel curve; (b) Nyquist plot; (c) Bode impedance modulus plot; (d) Bode phase angle plot

[0120] Figure 6 (a) Shows the corrosion resistance of the sample surfaces in each group. Except for the S and ST1 groups, the corrosion potentials of the remaining groups are not much different, all ranging from approximately -0.8 to -0.9 V.

[0121] It is worth noting that the corrosion potential of the surface treated with defocused laser irradiation (Group S) increased significantly, indicating that this process can significantly improve the corrosion resistance of the material surface. The nanocracks on the surface of Group S were not wide enough to allow the corrosive solution to penetrate and accelerate the corrosion of the substrate.

[0122] However, for the ST2 group, its surface texture increases the contact area between the metal and the external environment, resulting in uneven potential distribution on the metal surface, thus forming a large number of microbatteries. In addition, the surface of this group presents a hydrophilic state, which further accelerates the electrochemical corrosion process.

[0123] Therefore, the self-corrosion potential of the ST2 group is lower than that of the S group, indicating that its corrosion resistance is poor.

[0124] Compared with the grinding control group (P group), the S group did not have a clear passive zone and showed a higher corrosion current density, resulting in a lower polarization resistance. However, compared with the P group, the corrosion current density of the ST1 and ST2 groups decreased and the polarization resistance increased significantly.

[0125] This indicates that the corrosion rates of the ST1 and ST2 groups were lower than those of the other groups. This is because the microstructured substrate provides sufficient and effective contact area for the surface passivation process. However, the excessive contact area of the ST2 group also increases the number of active sites on the metal surface.

[0126] Figure 6 (b) shows the Nyquist plots for each group of samples. It can be seen that the capacitance ring radius of the ST1, S, and T1 groups is significantly larger than that of the grinding control group (P group). A larger radius means a lower corrosion rate. This indicates that the corrosion resistance of these three groups is superior to that of the P group, while there is no significant difference between the remaining groups and the P group. Among them, the composite structure of the ST1 group (shallow microstructure + nano-oxide film) shows the best corrosion resistance.

[0127] Figure 6 (c) is the Bode impedance modulus diagram. The higher the impedance value in the low-frequency region, the greater the resistance of the working electrode, indicating that a more stable oxide film has formed on the surface. Figure 6 (a)), Nyquist plot ( Figure 6 (b)) or Bode plot ( Figure 6 (c) The corrosion resistance of the ST1 group is the best. The microstructure promotes the formation of the passive film, and the nanofilm further causes a positive potential shift.

[0128] Figure 6(d) is a graph showing the relationship between phase angle and frequency. In the low to medium frequency range (1Hz–100Hz), the negative phase angle values of the laser-treated surface are significantly higher than those of the control group, indicating that the laser treatment increases the surface capacitance. In a wider frequency range (1Hz–1000Hz), the phase angle values of the ST1 and S groups are higher than those of the P group, indicating that these two groups form a stronger oxide layer on the surface. The enhanced surface capacitance allows more charge to be stored, forming a protective surface layer, thereby reducing the corrosion current density ( Figure 6 (a)), which plays the role of isolating or slowing down the erosion of artificial seawater.

[0129] Figure 7 The adhesion of Staphylococcus aureus to the surface of each group is shown: (a) P; (b) T1; (c) T2; (d) S; (e) ST1; (f) ST2. The colonies were counted using ImageJ software, and the inhibition rate of each group was calculated using the polished control group (P group) as the control group. Figure 7 As shown, the colonies of Staphylococcus aureus are round with clear edges. Statistical results show that the laser-treated surfaces have a significant inhibitory effect on Staphylococcus aureus. Among these samples, group T1 had the lowest actual inhibitory effect. The inhibition rates of the remaining groups all exceeded 84%.

[0130] Figure 8 SEM images of Staphylococcus aureus adhesion. (a) to (b) P; (c) to (d) T1; (e) to (f) T2; (g) S; (h) ST1; (i) ST2

[0131] Figure 8 The attachment status of Staphylococcus aureus on each group of surfaces is shown.

[0132] On the grinding surface (Group P), Staphylococcus aureus adhered in the form of biofilm and showed a certain directional arrangement ( Figure 8 (a)). As shown in the local enlarged image ( Figure 8 (b)), the biofilm mainly deposited on the rough texture of the surface, indicating that Staphylococcus aureus is more inclined to deposit and form biofilm on rough surfaces.

[0133] Figure 8 (c) shows the adhesion of Staphylococcus aureus to the surface of group T1. It can be observed that the bacteria mainly accumulate inside the shallow pits, but do not form a large-scale biofilm attachment like group P.

[0134] According to the Wenzel model formula: cosθ a =rcosθ Y , gives the intrinsic contact angle (denoted as θ Y ) and the apparent contact angle (denoted as θa ) is an analytical expression.

[0135] Because the surface roughness factor r is the smallest in group P, the intrinsic contact angle of the bacterial culture on the titanium alloy surface can be calculated to be approximately 63°. According to the formula, the theoretical apparent contact angle of group T1 should be 57.2°, but the actual measured contact angle is 105°, indicating that an air layer exists between the bacterial culture and the surface texture, hindering bacterial adhesion.

[0136] Therefore, the number of bacteria attached to the surface in group T1 was significantly reduced compared with group P.

[0137] In addition, when the bacterial adhesion is strong, it may be compressed in the vertical direction. Figure 8 (d) It can be seen that the number of bacteria falling into the shallow pit area is limited and still maintains a spherical shape, which indicates that the surface is in a Cassie state and can effectively hinder bacterial adhesion.

[0138] According to the Cassie-Baxter model formula cosθ a =f1cosθ Y -f2, the area fraction of solid and air per unit area can be calculated in more detail, where f1 (solid part) and f2 (air part), where: f1+f2=1

[0139] The calculation results showed that the f2 of group T2 was significantly higher than that of other groups, so its surface antibacterial effect was the most obvious.

[0140] Figure 8 (e) shows the attachment morphology of bacteria and biofilm on the deep pit array surface after laser treatment. Although there are a few biofilms in the micropores (such as Figure 8 (f)), but no obvious bacterial or biofilm attachment was observed in most areas.

[0141] It is worth noting that although the f2 values of the S group and the T1 group were similar, the amount of bacteria attached to the surface of the S group was significantly lower than that of the T1 group (see Figure 7 (b) with Figure 7 (d)). This suggests that the antibacterial activity of group S is not only due to its hydrophobicity, but may also be affected by its surface energy and nanostructure.

[0142] Figure 9 Images of live and dead bacterial cells. (a) G; (b) T1; (c) T2; (d) S; (e) ST1; (f) ST2 Figure 9 The distribution of live and dead cells on the surface of each group is shown. Live cells are stained green, while dead cells are stained red.

[0143] On the smooth grinding surface (P group), highly dense bacterial attachment was observed, accompanied by a large number of living cells, which is consistent with the Figure 9 The results are consistent with those of the cell attachment SEM images in (a).

[0144] On the surfaces of the T1 and T2 groups, although the number of cell attachments decreased, most cells were still alive, indicating that the microstructure had little effect on cell activity ( Figure 9 (b) with Figure 9 (c)).

[0145] Figure 10 The effect of detail size on cell membrane deformation parameters. (a) Schematic diagram; (b) L; (c) R; (d) ΔS / S0

[0146] The specificity of the S group (despite its f2 value being similar to that of the T1 group, its antibacterial activity was superior to that of the T1 group) may be due to its nanostructure. To this end, the antibacterial mechanism of the nanostructure was investigated. The following four equations relate to the process of contact between bacteria and nanostructures.

[0147]

[0148] Rp: radius of the nanopore (see Figure 10 (a))

[0149] h: Depth of the nanopore

[0150] ξ: number of nanopores per unit area

[0151] S0: original membrane surface area of bacteria, S0 = 4πR0 2

[0152] V0: original volume of bacteria, V0=4πR0 3 / 3

[0153] Figure (a) is a schematic diagram of some characteristic parameters of bacteria. Figure 10 (b)–(d) Analyze the effects of varying nanopit radius Rp and depth h on parameters L, R, and the degree of cell membrane stretch ΔS / S0. These three dependent variables reveal that as the pit radius increases, the bacterial cell membrane exhibits a stretched and deformed state, which promotes bacterial death. However, this bactericidal effect disappears when the nanopit radius exceeds a certain limit. In particular, when Rp ≥ 0.9 μm, the bactericidal effect is lost regardless of the pore depth. This suggests that the size of the bactericidal structure should be smaller than that of the bacteria.

[0154] SEM and AFM analysis revealed that the size of the nanocracks is sufficient to deform the cells. When the ratio of the cell membrane area change to the initial area (ΔS / S0) is between 0.15 and 0.3, the cell membrane can be effectively stretched to rupture. Of course, this process is also influenced by factors such as the tensile modulus, flexural modulus, and adhesion energy of the cell membrane.

[0155] Compared with the S group, the microstructured surfaces of the ST1 and ST2 groups showed higher hydrophilicity and enhanced their adhesion to the bacterial culture medium, which significantly aggravated the deformation of bacteria on the nanostructured surface and ultimately led to a significant reduction in the number of bacteria attached.

[0156] Figure 11 Optical images of marine fouling organisms attached to the surface of the material. (a) P; (b) T1; (c) T2; (d) S; (e) ST1; (f) ST2

[0157] Figure 11 The surface morphology of different samples after being immersed in seawater for 6 months is shown.

[0158] Figure 11 (a) shows the distribution of attached organisms on a smooth surface (Group P), showing a large number of nematodes. Because the smooth surface (Group P) lacks antimicrobial properties, bacteria easily attach and form biofilms, providing a suitable growth environment for nematodes.

[0159] In contrast, the main attachments on the surfaces of groups T1 and T2 were bryozoa (see Figure 11 (b) and 12(c)), with a small number of nematodes also visible. Bryozoans tend to attach in groups, forming a network-like structure. Their rapid growth allows them to form a dense attachment layer in a short period of time. On the other hand, surface roughness further degrades the material's antifouling properties. Figure 11 (b) and 12(c) also show that some nematodes are attached to the surface of the bryozoan.

[0160] The biofilm coverage in groups T1 and T2 was similar, but lower than that in group P. However, the coverage of bryozoans in groups T1 and T2 was higher than that in the control group.

[0161] Although the T2 group showed some antibacterial properties, its marine antifouling properties were not significant. The amount of bryozoans attached to its surface even exceeded that of the control group (P group) (see Figure 11 Although the T2 surface appears hydrophobic, the actual effect of seawater on the surface needs to be carefully considered. As the Weber number of the liquid increases, droplets can more easily penetrate the surface texture, thereby destroying its hydrophobicity.

[0162] For the S group, ST1 group and ST2 group, their data showed obvious similarity ( Figure 11 (d)(e)(f)) The biofouling area and dry weight of the bryozoan group were significantly reduced, with almost no bryozoan attachments. Furthermore, the bryozoan attachment area was significantly lower than that of the other groups.

[0163] Compared with the hydrophobic textured surface (T1 and T2 groups), the bactericidal effect of the nanostructure plays a key role in the antifouling process. The results show that the nanostructured surface with bactericidal ability has more durable antifouling and antibacterial properties than the microstructured surface. Overall, the shallow pit and nanostructured composite surface (ST1 group) has better corrosion resistance ( Figure 6 ), antibacterial properties ( Figure 7 ) and marine antifouling properties ( Figure 11 ) performed best.

[0164] Figure 12 SEM images of marine organisms attached to material surfaces. (a) Nematodes; (b) bryozoans; (c) barnacle glue; (d) biofilms, inorganic materials, and diatoms.

[0165] Figure 12 Images of several marine organisms clinging to the material were taken. Nematodes feed mainly on algae and bacteria as well as organic matter formed in the sediment (see Figure 12 (a)) Biofilm and bacteria grow on surfaces lacking antimicrobial properties, thereby inducing nematode attachment. Figure 12 (b) It can be seen that bryozoans tend to attach in groups, forming a network structure. They grow rapidly and can form a dense attachment layer in a short period of time. Figure 12 (d) The biofilm formed by bacterial aggregates causes barnacle larvae to adhere and grow into adults on it (Figure (c)).

[0166] In summary:

[0167] 1. Corrosion resistance

[0168] Potentiodynamic polarization test (PDP):

[0169] The polarization resistance of group ST1 is the highest, reaching 66676Ω·cm 2 , indicating that it has the strongest corrosion resistance.

[0170] The corrosion current of group ST1 is the lowest, which is 1.451×10 -5 A, further confirms its low corrosion rate.

[0171] The self-corrosion potential of group ST1 is -0.386 V, which is significantly higher than that of other groups, indicating that a more stable oxide layer has been formed on its surface.

[0172] Electrochemical Impedance Spectroscopy (EIS):

[0173] The radius of the capacitance ring in the Nyquist plot of group ST1 is the largest, indicating that its corrosion resistance is better than that of other groups.

[0174] The impedance value of group ST1 is the highest in the low-frequency region, which further confirms that the oxide layer formed on its surface is the most stable.

[0175] 2. Antibacterial properties

[0176] Bacterial adhesion assay:

[0177] The number of bacteria adhering to group ST1 was significantly reduced, and the antibacterial effect was significant.

[0178] The contact angle of group ST1 was 105°, indicating that its surface had good droplet repelling properties, reducing bacterial adhesion.

[0179] The surface nanostructure of group ST1 can effectively destroy bacterial cell membranes, further reducing bacterial adhesion and activity.

[0180] Live and dead cell staining:

[0181] The number of living cells on the surface of group ST1 was significantly reduced, indicating that it had a good bactericidal effect.

[0182] 3. Marine antifouling performance

[0183] Seawater immersion experiment:

[0184] Group ST1 had the least surface attached biomass and the lowest dry weight, with almost no nematodes attached.

[0185] The surface of group ST1 showed almost no obvious bioattachment after immersion, indicating its excellent antifouling performance.

[0186] 4. Surface morphology

[0187] The surface of group ST1 combines shallow micropits and nanostructures, with a micropit depth of 18.38 μm, a width of 28.79 μm, and a surface roughness (Ra) of 1.85 μm.

[0188] While the surface of group ST1 maintains the microtexture morphology, the presence of nanostructures further enhances the antibacterial and antifouling properties of the surface.

[0189] 5. Comprehensive advantages

[0190] The micro-nano composite structure of group ST1 exhibits significant advantages in corrosion resistance, antibacterial properties, and marine antifouling properties. The surface properties of group ST1 give it broad application prospects in complex application environments (such as marine environments and medical implants).

[0191] Overall, ST1 (shallow pits + nanostructure) performed best in corrosion resistance, antibacterial properties and marine antifouling properties, and was the surface treatment method with the best performance among all experimental groups.

[0192] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are within the scope of the technical solution of the present invention.

Claims

1. A method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure, characterized in that: The following steps are involved: S1, pretreatment of titanium alloy plate; S2, nanosecond laser processing of titanium alloy plate to prepare microtexture; S3. The titanium alloy plate is subjected to laser defocused irradiation processing to prepare a nanostructure, thereby forming a composite structure on the surface of the titanium alloy plate.

2. The method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure according to claim 1, characterized in that: The S1 step specifically includes: s1. Cutting: Use laser cutting machine to cut materials; s2. Grinding: Use a surface grinder to grind the material surface until the roughness Ra is less than 0.1μm; s3. Cleaning: Use ethanol and deionized water to clean the material in an ultrasonic cleaner for 10 minutes; s4. Drying: Let the material dry naturally.

3. The method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure according to claim 1, characterized in that: The method further includes a detection step, which specifically includes: A. Cutting to form samples; B. Surface morphology analysis; C. Surface chemical analysis; D. Corrosion resistance test; E. Bacterial adhesion test; F. Seawater immersion test; G. Statistical analysis.

4. The method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure according to claim 3, characterized in that: The step A specifically includes: Three sample groups of 10 mm × 10 mm × 1 mm, 20 mm × 20 mm × 1 mm, and 35 mm × 45 mm × 3 mm were cut from the material; 10 mm × 10 mm × 1 mm samples were used for surface morphology analysis, surface chemistry analysis, and corrosion resistance testing; Samples of 20 mm × 20 mm × 1 mm were used for bacterial adhesion testing; A 35 mm × 45 mm × 3 mm sample was used for the ocean immersion test and a hole with a diameter of 3 mm was drilled on one edge.

5. The method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure according to claim 4, characterized in that: The surface morphology analysis includes scanning electron microscopy, ultra-depth of field microscopy and atomic force microscopy; the scanning electron microscopy is used to observe the surface morphology of the sample, and the acceleration voltage is 15kV; Ultra-depth-of-field microscopy is used to measure the average roughness, depth and diameter of the microtexture of the sample; atomic force microscopy is used to evaluate the surface roughness and geometric dimensions of the nanostructure of the sample.

6. The method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure according to claim 4, characterized in that: The surface chemical analysis includes X-ray photoelectron spectroscopy and X-ray diffraction. The X-ray photoelectron spectroscopy is used to analyze the chemical composition of the sample surface, including narrow spectra of C1s, Ti2p and O1s; and the X-ray diffraction is used to determine the phase composition of the sample.

7. The method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure according to claim 4, characterized in that: The corrosion resistance test includes a corrosion performance potentiodynamic polarization test and an electrochemical impedance spectroscopy test. The corrosion performance potentiodynamic polarization test uses an electrochemical workstation; the corrosion solution is artificial seawater, which contains 25.5g / L sodium chloride, 3.2g / L magnesium sulfate, 1.3g / L calcium chloride, and 0.7g / L potassium chloride. In the test system, a carbon rod serves as a working electrode, Ag / AgCl serves as a reference electrode, and the sample serves as a working electrode. The scan rate is 5mV / s, and the scan range is -1400mV to 400mV. The sample needs to be immersed in the corrosion solution for 30 minutes before the test is terminated, and the equilibrium potential, corrosion current, cathode Tafel slope, anodic Tafel slope, and polarization resistance Rp are calculated by extrapolation. The electrochemical impedance spectroscopy test is performed in a frequency range of 100 kHz to 1 Hz, with a sinusoidal potential change of 5 mV applied to the sample.

8. The method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure according to claim 4, characterized in that: The E step specifically includes: Bacterial adhesion: Titanium alloy was placed in a 24-well plate and incubated at 121°C, 1.1×10 5 Sterilize in an autoclave at a pressure of Pa for 20 min; select Staphylococcus aureus and culture it in Luria-Bertani medium for 18 h; dilute the bacterial colony to 1×10 6 A bacterial suspension was formed in fresh culture medium with a concentration of 100 CFU / mL; 300 μL of the bacterial suspension was added to the well plate and incubated at 37°C for 24 hours; 20 μL of the incubated bacterial suspension was aspirated as a sample; each sample was washed with PBS and sonicated in 10 mL of normal saline for 5 minutes; 100 μL of the bacterial suspension was removed from each sample and cultured on an agar plate to determine the antibacterial properties; the suspension on the sample in the well plate was removed at the same time, and the bacteria on the sample surface were fixed with 3% glutaraldehyde; the sample was dehydrated using a gradient dehydration method; the metal surface was gold-plated, and the morphology of the bacteria was observed using a scanning electron microscope; Bacterial cell viability test: Combined with SYTO 9 green fluorescent nucleic acid dye and propidium iodide, the survival rate of bacterial cells on different surfaces of the sample was evaluated; Contact angle measurement: Use a contact angle meter to obtain images of the contact state of the bacterial suspension on the material surface.

9. The method for preparing an antibacterial and corrosion-resistant titanium alloy surface composite structure according to claim 4, characterized in that: The F step includes: Before immersing in seawater, the samples were weighed in a dry state; the samples were suspended in the seawater, more than 0.5 meters below the water surface at low tide. After 6 months of testing, the samples were removed from the seawater, dried, and weighed again; after weighing, the sample surface was gold-plated, and the morphology of the attached organisms on the sample surface was observed using a scanning electron microscope, and the length, area, and number of the main attached organisms were quantified using ImageJ software.